2015
DOI: 10.3126/njst.v15i2.12118
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of Drought in Far and Mid Western Regions of Nepal: Time Series Analysis (1982-2012)

Abstract: Recent and potential future increases in global temperature are likely to be associated with impacts on the hydrological cycle, including changes to precipitation and increases in extreme events such as droughts. This study has investigated the spatial and temporal changes in drought occurrence in far and mid-western regions of Nepal. Quantification of the severity and frequency of drought within different physiographical regions have been worked out with the help of Standardized Reconnaissance Drought Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…The trend analysis of SPI magnitude showed a decreasing tendency, indicating increasing drought, which is more evident at the longer time scale. Even there is limited study concerning drought trend in Nepal, evidence of increased occurrence of drought due to precipitation deficit is consistent with the results presented by previous researchers (Kafle 2014;Sigdel and Ikeda 2010;Wang et al 2013) Several studies (Chang and Kleopa 1991;Heim 2002;Paulo and Pereira 2006) have shown that precipitation is the main variable determining drought condition; however, many empirical studies (Hu and Willson 2000;Rebetez et al 2006;Vicente-Serrano et al 2009) Nat Hazards (2016) 80:1913-19321927 have shown that rise in temperature has important effects on the severity of droughts conditions. Figure 12 shows that there is increasing trend of temperature in all region of central Nepal in past.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The trend analysis of SPI magnitude showed a decreasing tendency, indicating increasing drought, which is more evident at the longer time scale. Even there is limited study concerning drought trend in Nepal, evidence of increased occurrence of drought due to precipitation deficit is consistent with the results presented by previous researchers (Kafle 2014;Sigdel and Ikeda 2010;Wang et al 2013) Several studies (Chang and Kleopa 1991;Heim 2002;Paulo and Pereira 2006) have shown that precipitation is the main variable determining drought condition; however, many empirical studies (Hu and Willson 2000;Rebetez et al 2006;Vicente-Serrano et al 2009) Nat Hazards (2016) 80:1913-19321927 have shown that rise in temperature has important effects on the severity of droughts conditions. Figure 12 shows that there is increasing trend of temperature in all region of central Nepal in past.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies in Nepal have focused on the spatial pattern and temporal progression of drought events and its linkages between some climate indices and atmospheric circulation pattern (Kafle 2014;Sigdel and Ikeda 2010;Wang et al 2013), and for annual seasonal periods. There has been no investigation for the period of crop growing seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, increasing CDD observed over the study area is consistent with the most widespread and worst drought observed in recent decades across the country [99,101,110,111]. Rise in CDD clearly indicates the prolongation of the dry period across the country, implying certain changes in the seasonality of prevailing precipitation regimes [95,96].…”
Section: Dry and Wet Spellssupporting
confidence: 52%
“…Based on the coarse resolution Global Precipitation Climatology Project (GPCP) dataset, Yao et al [113] have also provided evidence of decreasing precipitation over all the Himalayas and an increase in the eastern Pamir regions during 1979-2010. factors besides precipitation. Nevertheless, increasing CDD observed over the study area is consistent with the most widespread and worst drought observed in recent decades across the country [99,101,110,111]. Rise in CDD clearly indicates the prolongation of the dry period across the country, implying certain changes in the seasonality of prevailing precipitation regimes [95,96].…”
Section: Extra Indices (Prcptot Sdii and Wd)supporting
confidence: 52%
“…Nepal droughts over the last 33 years had moderate to extreme drought intensity in Nepal [12]. Drought often occurred in mid and far western Nepal [13], especially during the winter and summer season [14]. The worst widespread droughts in central Nepal were recorded in 2004, 2005, 2006, 2009 in summer and 2006, 2008 and 2009 in winter [15].…”
Section: Introductionmentioning
confidence: 99%